Seedling survival of Handroanthus impetiginosus (Mart ex DC) Mattos in a semi-arid environment through modified germination speed and post-germination desiccation tolerance - J. R. Martins; A. A. S. Edvaldo; A. A. Alvarenga; A. C. Rodrigues; D. E. Ribeiro; P. E. Toorop (Brazilian Journal of Biology)
Abstract Uniform rapid seed germination generally forms a great risk for the plant population if subsequent intermittent precipitation causes desiccation and seedling death. Handroanthus impetiginosus can be found commonly in a wide range of biomes within Brazil including those that are semi-arid. Germination and early growth was studied to understand how germinated seeds survive under these stringent conditions. Accessions were sampled from four seasonally dry biomes in Brazil. Precipitation at the start of the rainy season in the Caatinga, a semi-arid biome, is less predictable and the number of successive dry days per dry interval in the first four months of the rainy season was higher than in the other studied biomes. Plants from the Caatinga produced thicker seeds and this trait concurred with slow germination and stronger osmotic inhibition of germination across the accessions, forming a stress avoidance mechanism in the Caatinga. Post-germination desiccation tolerance was high in the Caatinga accession, could be re-induced in accessions from biomes with more regular precipitation (Cerrado and transition zone), but remained poor in the Cerradão accession; thus forming a stress tolerance mechanism. Production of adventitious roots ascertained survival of all tested individuals from all four locations, even if protruded radicles did not survive desiccation, forming an additional stress tolerance mechanism. A sequence of stress avoidance and stress tolerance mechanisms in seeds and germinated seeds was associated with precipitation patterns in different biomes. These mechanisms purportedly allow rapid seedling establishment when conditions are suitable and enable survival of the young seedling when conditions are adverse.